Fatigue among traffic police officers in metropolitan city: exploring factors of noise exposure and work stressors - Rasdi, Irniza; Din, Nur Fatihah; Roni, Nurulizyati; Isha @ Isa, Ahmad Shahrul Nizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Police work has been recognised worldwide as a very stressful job. Those especially in road traffic control department encounter an additional possible cause of fatigue which is noise exposure that rarely being explored. Methods: A cross-sectional study was conducted among traffic police officers in Kuala Lumpur to assess their level of fatigue and its risk factors including noise exposure, work stressors and individual factors. A total of 171 traffic police officers in Kuala Lumpur participated in this study. A set of questionnaires on socio-demographics, work characteristics, perception regarding noise pollution, PSQ and CIS were distributed to 200 traffic police officers in Kuala Lumpur. Five locations with heavy traffic volume in Kuala Lumpur were selected for ambient noise measurement, three times a day during peak hour by SLM. Results: The mean age, job tenure and BMI of respondents was 30.49±7.12yo, 4.73±4.62 years and 24.83 respectively. Most of them were Malay (81.9%), married (60.8%), and secondary school graduated (84.8%). The traffic noise exposure levels ranged between 69.50 dB(A) to 82.80 dB(A) (mean = 76.77±4.39 dB(A). Almost 20% of respondents reported to have fatigue level that puts them at risk for subsequent work disability. After considering several potential factors, lower educational levels (β=-3.67, p <0.01) and doing part time job (β=0.16, p=0.03) was found significant in predicting more fatigue. Conclusion: In sum, findings provide baseline data on the main factors of fatigue among this young and normal weight police group which will help in prioritizing the intervention strategies.